Government Supervision In Overcoming Problems Drinking Tuak At The Gunung Meriah Aceh - Khairuddin Khairuddin (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
The people of Gunung Meriah still find many addictions to drinks that can be intoxicating, such as drinking tuak. Therefore, this study aims to find out how the supervision of the government and the community in minimizing wine drinkers and sellers in Gunung Meriah District and Islamic views on the law of drinking tuak, as well as how to sanction those who drink it. To complete this research, the writer uses qualitative research. The techniques used in data collection are observation and in-depth interviews with informants. The result of the research shows that some of the people of Gunung Meriah like to drink tuak, both from officials and ordinary people. 25% of Mount Meriah people are addicted to this tuak drink, it is drunk on certain occasions such as parties or other days. The government does not pay much attention to the problem of tuak drinks, which can be seen from the lack of cases of drinkers and sellers of wine being appointed and given appropriate punishments, only a few people have reached the stage of punishment. Likewise, the community does not interfere too much in dealing with the problem of tuak drinkers and sellers, even though this problem is very serious. Drinking tuak, in the perspective of Islamic law, is a drink that is prohibited because it is intoxicating.